The Influence of Corporate Social Responsibility (CSR) and Cost of Debt on Corporate Financial Performance during the Covid-19 Pandemic with Political Connections as a Moderating Variable - Lidya Agustina; Etty Murwaningsari (Sekolah Tinggi Ilmu Ekonomi Sutaatmadja, 2022)
This study aims to examine the effect of corporate social responsibility and the cost of debt on the company's financial performance, as well as to examine whether political connections can moderate the effect of corporate social responsibility and the cost of debt on the financial performance of companies listed on the IDX for the 2019-2020 period. Based on 193 companies, and 386 processed panel data, the results showed that corporate social responsibility had a positive and significant effect on the company's financial performance, while the cost of debt had a negative and significant effect on the company's financial performance. However, political connections did not succeed in moderating the effect of social responsibility and the cost of debt on the company's financial performance. This could be due to the two sides of political connections, where there is convenience because these political connections can have an impact on increasing the company's debt structure, thus making the company burdened where the company's profit will decrease due to having to pay off its debt burden.